FE homogenised limit analysis model for masonry structures - Milani, Gabriele (2011)
A finite-element (FE) homogenised limit analysis model suitable for analysing masonry structures near collapse is applied to a real large-scale three-dimensional (3D) masonry building subjected to horizontal actions. In the model, masonry is substituted for a fictitious macroscopic homogeneous material. Masonry macroscopic mechanical properties are obtained by means of a recently presented equilibrated limit analysis approach performed on a suitable unit cell, which generates the entire structure by repetition. Masonry homogenised failure surfaces are then implemented in the 3D code outlined. With respect to previously presented models, the software allows analysis of real-scale buildings without the classic uncoupling of in-plane and out-of-plane actions. The possible presence of steel, reinforced concrete and ring beams is also considered by introducing two-node beam elements in the numerical model. A relevant 3D structural example (a masonry structure subjected to horizontal actions) is treated. Full sensitivity analyses and comparison with results obtained from commercial elasto-plastic software are also presented to validate the results of the proposed model.